The Association Between Preeclampsia and Low Birth Weight in Hospitals in Medan: A Case-Control Study - Aidil Akbar; Muhammad Solih Nasution; Alltop Amri Ya Habib (Universitas Islam Negeri Sumatera Utara, Medan, 2026)
Preeclampsia is a medical condition that causes increased blood pressure occurring during pregnancy, which significantly contributes to poor prenatal outcomes, such as low birth weight (LBW). In Indonesia, especially in North Sumatra, the prevalence of preeclampsia remains significant; however, data concerning its correlation with low birth weight in hospital environments is still scarce. This research was intended to ascertain the correlation between preeclampsia and the incidence of low birth weight among mothers delivering in hospitals in Medan City. A hospital-based case–control study utilized secondary data from medical records at H. Adam Malik Hospital and Dr. Pirngadi Hospital, Medan, from January 2022 to June 2024. A total of 180 postpartum women participated, comprising 90 cases (women who gave birth to babies with low birth weight) and 90 controls (women who gave birth to babies with normal birth weight). We used multivariable logistic regression and chi-square testing to find adjusted odds ratios (ORs) with 95% confidence intervals (CIs). A strong link existed between low birth weight and preeclampsia. Mothers with preeclampsia exhibited a significantly elevated probability of delivering low birth weight infants in comparison to those without preeclampsia (adjusted OR = 6.21; 95% CI: 3.10–12.30; p < 0.001). Advanced maternal age (>35 years) and preterm gestational age (<37 weeks) were independently correlated with low birth weight (LBW), whereas parity exhibited no significant correlation. Preeclampsia is significantly correlated with the incidence of low birth weight in mothers delivering in hospitals in Medan City. To improve maternal and child health and lower the risk of bad outcomes for newborns, it is important to improve early detection and comprehensive antenatal management of preeclampsia. Keywords: Preeclampsia, Low Birth Weight, Maternal Age, Gestational Age, Case-Control Study.